Surface and interfacial forces - Butt, Hans-Jürgen; Kappl, Michael, 1963- (Wiley-VCH, 2018)
This systematic introduction to the topic includes theoretical concepts to help readers understand and predict surface forces, while also integrating experimental techniques and practical applications with up-to-date examples plus motivating exercises.